Unknown unknowns an introduction to mysteries : saggi - Coccia, Emanuele 1976-; Ayache, Elie 1966-; Boeri, Stefano 1956-; Cassé, Michel 1943-; Hester, Helen 1983-; Joler, Vladan; Kirksey, Eben 1976-; Marletto, Chiara; Mineko Ichioka, Sarah; Quinz, Emanuele 1973-; Spanò, Michele; Venturi, Riccardo 1974- (Electa, 2022)
The exhibition is accompanied by two publications, containing Essays and a Catalogue (both with graphic design by 2×4 in New York) respectively. They serve as an add-on to the curatorial approach, an exhibition "within" and "beyond" the exhibition. This publication features the essays. Introduced by Stefano Boeri and Emanuele Coccia, it contains several theoretical contributions written by internationally acclaimed writers – Elie Ayache, Michel Cassé, Manuele Fior, Helen Hester, Vladan Joler, Eben Kirksey, Chiara Marletto, Sarah Mineko Ichioka, Emanuele Quinz, Michele Spanò and Riccardo Venturi – professionals, experts, scholars and researchers in different fields of knowledge. The essays present contemporary phenomena from diverse angles: political-philosophical, creative, scientific-biological, economic and statistics… with a view to conveying the critical drive behind the International Exhibition. This first volume seeks to trigger a debate on the "unknown unknowns" all around us
Collected essays published on the occasion of 23nd Triennale di Milano. - Impressum: 23a Esposizione Internazionale di Triennale Milano "Unknown Unkowns. An Introduction to Mysteries", 15 luglio - 11 dicembre 2022
Keywords: Triennale -- Mailand; Ästhetik; Aufsatzsammlung